Oxford studies in metaethics - Shafer-Landau, Russ (Clarendon Press ; Oxford University Press, 2006)
Oxford Studies in Metaethics is the only periodical publication devoted exclusively to original philosophical work on the foundations of ethics. It provides an annual selection of much of the best new scholarship in the field. Its broad purview includes work at the intersections of ethical theory with metaphysics, epistemology, philosophy of language, and philosophy of mind. OSME provides an excellent basis for understanding recent developments. in the field; those who would like to acquaint themselves with the current state of play in metaethics would do well to start here. - ; Oxford Studies.